COLOR VISION DEFECT: COLOR BLINDNESS: रंग दृष्टि दोष: रंग अंधता - Shakya, Sudha (International Journal of Research -GRANTHAALAYAH, 2014)
Humans have many types of sensations such as sight, hearing, touch, smell, taste etc. They originate from stimulants, which a person receives from their external environment, stimulate the stimulating senses i.e. eye, ear, skin, nose and tongue, and produce different sensations. According to Eiseneck (1972), "sensation is a mental process that is no longer divisible." It is produced by external stimuli that affect the senses, and its intensity depends on the stimulus, and its properties depend on the nature of the senses. Apart from these five sensations, there are other sensations such as incidental sensation, static sensation and motion sensation. मानव में कई प्रकार की संवेदनाएं होती हैं जैसे दृष्टि, श्रवण, स्पर्श, गंध, स्वाद आदि। इनकी उत्पत्ति उद्दीपकों से होती है, जिसे व्यक्ति अपने बाह्य पर्यावरण से ग्रहण करता है, यह उद्दीपक ज्ञानेन्द्रियों अर्थात आंख, कान, त्वचा, नाक और जिव्हा को उद्दीप्त करते हैं, और विभिन्न संवेदना को उत्पन्न करते हैं। आइजनेक (1972) के अनुसार ‘‘ संवेदना एक मानसिक प्रक्रम है जो आगे विभाजन योग्य नहीं होता। यह ज्ञानेन्द्रियों को प्रभावित करने वाली बाह्य उत्तेजना द्वारा उत्पादित होता है, तथा इसकी तीव्रता उत्तेजना पर निर्भर करती है, और इसके गुण ज्ञानेन्द्रिय की प्रकृति पर निर्भर करते हैं। इन पांच संवेदनाओं के अतिरिक्त अन्य संवेदना भी है जैसे आंगिक संवेदना, स्थैतिक संवेदना तथा गति संवेदना।